1999
DOI: 10.1034/j.1399-6576.1999.430502.x
|View full text |Cite
|
Sign up to set email alerts
|

Do blood levels of neuron‐specific enolase and S‐100 protein reflect cognitive dysfunction after coronary artery bypass?

Abstract: NSE seems to be a useful blood marker for early cognitive dysfunction after coronary artery bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
68
4
16

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 20 publications
(25 reference statements)
11
68
4
16
Order By: Relevance
“…Martens et al (27) described that S100 correlated significantly with bypass time, cross clamp time and lowest temperature during CPB, probably due to the use of non-pulsatile CPB. Rasmussen et al (28) reported that S100 at 24 hours correlated well with the duration of CPB, but not with measures of cognitive dysfunction. From the present study, we may find two peaks of serum S100 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Martens et al (27) described that S100 correlated significantly with bypass time, cross clamp time and lowest temperature during CPB, probably due to the use of non-pulsatile CPB. Rasmussen et al (28) reported that S100 at 24 hours correlated well with the duration of CPB, but not with measures of cognitive dysfunction. From the present study, we may find two peaks of serum S100 protein.…”
Section: Discussionmentioning
confidence: 99%
“…[50] hem S100b hem de NSE değerlerinin cerrahi süresi, perfüzyon ve kros-klemp süresinden bağımsız olduğunu bildirmişlerdir. Rasmussen ve ark.na [51] göre serum S100b düzeyindeki artış, KPB süresi ile ilişki-lidir. Gu ve ark.…”
Section: Nöron Spesifik Enolazunclassified
“…Erken dönemde (KPB'den sonra ilk 5 saat) yaş, dolaşım arresti ve KPB süresi, aort kros-klemp zamanı, ameliyat öncesi serebrovasküler hastalıklar, aort kanülasyonu sırasında oluşan emboli sayısı, ameliyat sonrası serebral komplikasyonlar ve ameliyat öncesi renal hasar; geç dönemde (KPB'den sonra 15-48 saat arası) perioperatif serebral komplikasyonlar, dolaşım arresti ve serebral perfüzyon yokluğunun süresi, çıkan aort aterosklerozu ve yenidoğanlar gibi etkenlerin etkili olduğu Hemoliz Nöron spesifik enolaz artar, S100b etkilenmez [41] Kardiyotomi aspirasyon S100b artar, nöron spesifik enolaz etkilenmez [9] Koroner arter baypas greftleme, kapak replasman cerrahisi Nöron spesifik enolaz ve S100b artar [40] Kardiyopulmoner baypas Nöron spesifik enolaz ve S100b artar [45] Aprotinin Nöron spesifik enolaz ve S100b etkilenmez [9] MgSO 4 infüzyonu S100b azalır, nöron spesifik enolaz bilinmiyor [43] Dopamin infüzyonu S100b artar, nöron spesifik enolaz bilinmiyor [43] Heparin, protamin, propofol S100b etkilenmez, nöron spesifik enolaz bilinmiyor [44] Metilprednizolon Nöron spesifik enolaz azalır, S100b bilinmiyor [45] Kardiyopulmoner baypas süresi Nöron spesifik enolaz ve S100b artar [21,47] Nöron spesifik enolaz etkilenmez [45] S100b artar [51] Off-pump koroner arter baypas greftleme S100b azalır, nöron spesifik enolaz bilinmiyor [47] Pulsatil akıma karşı nonpulsatil akım S100b etkilenmez, nöron spesifik enolaz bilinmiyor [46] S100b azalır, nöron spesifik enolaz bilinmiyor [49] Yaş S100b etkilenmez [48 Nöron spesifik enolaz ve S100b artar [21] Perfüzyon süresi S100b artar [34] S100b etkilenmez [48] Aort kros-klemp zamanı S100b etkilenmez [48] Nöron spesifik enolaz ve S100b etkilenmez [50] Nöron spesifik enolaz ve S100b artar [21] Yoğun bakımda yatış süresi, cinsiyet S100b etkilenmez, nöron spesifik enolaz bilinmiyor [48] Cerrahi süresi Nöron spesifik enolaz ve S100b etkilenmez [50] Apoe4 alleli Nöron spesifik enolaz ve S100b artar [54] düşünülmektedir. [24] Özatik ve ark.…”
Section: Nöron Spesifik Enolazunclassified
See 1 more Smart Citation
“…POCD is characterized by impairment of recent memory, concentration, language comprehension, and social integration. 1,2 This syndrome may be detected days to weeks after surgery and may even be permanent. 3 Although POCD is most frequent after cardiac surgery, the prevalence of POCD after noncardiac surgery in older patients is also significant (25% at 1 week, 10% at 3 months after surgery).…”
mentioning
confidence: 99%